The Importance of Parenting Patterns in the Development of Emotional Intelligence in Elementary School Students - Mardiah, Ainul; Nisa, Sahrun; Suriani, Ari (PT FORMOSA CENDEKIA GLOBAL, 2024)
Parenting is very important for the growth of the emotional intelligence of elementary school students. The purpose of this study is to find out how important appropriate parental behavior is in helping the development of children's emotional intelligence. The method used was the collection and analysis of ten nationally accredited journal articles related to the topic. The results showed that democratic parenting that involves child involvement and emotional support can help children grow positive emotional intelligence. In contrast, authoritarian or permissive parenting tends to inhibit the development of children's emotional intelligence. These findings confirm that parents play an important role in shaping students' emotional intelligence by implementing effective parenting. Thus, understanding and implementing appropriate parenting strategies by parents so that children can develop good emotional intelligence for future success.